Perlindungan Hukum Bagi Korban Pelecehan Seksual Cat Calling Pada Perempuan Di Lingkungan Kampus Universitas Bengkulu - Saur Bakti Boru Manurung; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Campus life is an important phase for students in developing themselves, both academically and socially. However, many students, especially women, face the risk of sexual harassment, including catcalling, which can disrupt their comfort and safety in the campus environment. Catcalling, which includes sexual comments and attention without consent, is often taken lightly, even though it can cause serious psychological impact to the victim. The purpose of this study is to bring awareness to the phenomenon of catcalling and its role in creating an unsafe environment for university students. In Indonesia, Law No. 12 of 2022 provides legal protection against sexual violence through handling, protection, and recovery, but enforcement and socialization still face various challenges. Although many campuses have adopted anti-harassment policies, the implementation of these regulations is often hampered by the lack of effective reporting mechanisms and legal understanding among students. This research emphasizes the need for more intensive education as well as clear legal support to provide a safe and comfortable environment for everyone within.